ISLAMIC ASSESSMENT OF THE EFFECTS AND CONSEQUENCES OF GAME OF LOTTERY ON THE PEOPLE OF AKWANGA, NASSARAWA EGGON AND WAMBA, NASARAWA STATE, NIGERIA - Dahiru, Ibrahim Shekarau; Nasidi, Shuaibu Mahmud (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2025)
This study provides an Islamic assessment of the effects and consequences of playing the lottery in Akwanga, Nassarawa Eggon, and Wamba, Nasarawa State, Nigeria. Recently, there has been a global surge in lottery and betting activities, with Nigeria experiencing significant growth in this sector. Akwanga, Nassarawa Eggon, and Wamba are no exception, as many Muslim youths actively participate in these games of chance despite Islam’s strict prohibition. This phenomenon is partly attributed to the high unemployment rate in the country. Using a qualitative approach, the study collects primary data through interviews and focus group discussions with lottery players, Islamic scholars, and community leaders. The findings reveal that lottery and betting activities have severe economic, social, and moral consequences, contradicting Islamic teachings. The study concludes that Islamic principles and values can serve as a framework for understanding the negative impacts of gambling and promoting alternative forms of economic empowerment and social welfare. The study recommends collaboration between Islamic scholars, community leaders, and policymakers to raise awareness about the dangers of gambling and to promote Islamic values as a solution to economic and social challenges. Additionally, it suggests that the government impose heavy taxes on gambling, betting, and lottery establishments in the study area to curb the spread of this practice.